2015
DOI: 10.1177/0310057x1504300306
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of an Increased in Vitro Thrombotic and Bleeding Tendency in Critically Ill Trauma and Non-Trauma Patients

Abstract: Trauma patients are at a high risk of both bleeding and thromboembolism. This study assessed whether conventional coagulation blood tests were reliable predictors of an increased in vitro thrombotic and bleeding tendency of trauma and non-trauma patients. Conventional coagulation blood tests and thromboelastographs of 63 trauma and 63 randomly selected, critically ill non-trauma patients were compared. Increased in vitro thrombotic and bleeding tendencies were defined by a maximum amplitude >72 mm or an angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Of the 4963 studies identified in the databases, 41 studies from 14 countries, including 10,818 patients in a variety of clinical settings, met the inclusion criteria and were subject to meta‐analysis (Figure ) . A list of the studies excluded and the reasons for their exclusion are summarized in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 4963 studies identified in the databases, 41 studies from 14 countries, including 10,818 patients in a variety of clinical settings, met the inclusion criteria and were subject to meta‐analysis (Figure ) . A list of the studies excluded and the reasons for their exclusion are summarized in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…The plasma fibrinogen concentration is often the first coagulation factor to reduce to a pathological low level in critical bleeding 63 , and it is also a major determinant of the thickness of the viscoelastic test tracing (e.g. maximal amplitude) 4,8 . In this way, the thickness can be used to guide correction of fibrinogen levels with fibrinogen concentrate or cryoprecipitate if they are used to manage critical bleeding, although laboratory measurement of plasma fibrinogen concentration would be more accurate and specific as the thickness of viscoelastic tracing is also influenced by platelets.…”
Section: Viscoelastic Tests and The Cell-based Coagulation Modelmentioning
confidence: 99%
“…This pathological feature suggests that patients with thrombotic microangiopathy are intrinsically prothrombotic. If this is the case, it may be possible to use viscoelastic point-of-care devices such as TEG® to confirm the associated hypercoagulability with a reduced r-time or increased maximum amplitude (MA), similar to patients with trauma, sepsis, or heparin-induced thrombocytopenia syndrome [2][3][4] .…”
Section: Thromboelastometry and Thromboelastography Failed To Detect mentioning
confidence: 99%